March of the wooden soldiers [videorecording (DVD)] - Roach, Hal, 1892-1992; Butler, Frank, 1890-1967; Grinde, Nick, 1894-1979; Meins, Gus, 1893-1940; Rogers, Charles, 1887-1956; Laurel, Stan; Hardy, Oliver, 1892-1957; Herbert, Victor, 1859-1924 (Holiday classics collection (Metro-Goldwyn-Mayer (1992- )), 2007)
Musical comedy with Laurel and Hardy in a story that takes them to Toyland where they try to help Little Bo Peep escape the evil clutches of Barnaby and his band of Boogeymen.